Predictive Values of Inflammation-Related Markers and Thyroid Function in Pediatric Thyroid Cancer Patients - Li, Shuo; Liu, Yihao; Liu, Shaoxuan; Du, Gongbo; Wang, Zipeng; Yin, Detao (Frontiers in Pediatrics, 2021)
Few researchers have studied the diagnostic value of inflammation-related hematological indexes of pediatric thyroid carcinoma exclusively. Whether thyroid-stimulating hormone (TSH) is an independent risk factor for pediatric thyroid cancer is still controversial. To assess the correlativity and predictive values of inflammation-related markers and thyroid function in pediatric thyroid cancer patients, we collected a total of 270 children with thyroid nodules for two consecutive years. Clinical data including age, gender, thyroid function, inflammation indexes and clinical pathologic finding were collected and analyzed. The above-mentioned data were compared between the benign group and the malignant group, followed by the subgroups comparison. Binary logistic regression analysis was used to evaluate the correlation of markers and the pathological features of thyroid nodules. The neutrophil-to-lymphocyte ratio (NLR) showed a significant difference between thyroid cancer and thyroid nodules, while TSH did not. NLR>1.49529 was the prognostic indicator of pediatric thyroid cancer. The logistic regression model further revealed that NLR>1.49529 was an independent risk factor for thyroid cancer in pediatric patients. Furthermore, TSH was not correlated with the tumor characteristics in the thyroid cancer group. In conclusion, the findings in this study showed that NLR could be a predictor of thyroid cancer in pediatric patients and refuted the present view that TSH is a risk factor in pediatric thyroid cancer.